Multicenter Study Evaluating Performance of the Smart Group B Streptococcus (GBS) Assay Using an Enrichment Protocol for Detecting GBS Colonization in Patients in the Antepartum Period - Jordan, Jeanne A; Hall, Geraldine; Davis, Thomas (Journal of Clinical Microbiology, 2010)
Group B streptococcus (GBS) remains the leading cause of infectious morbidity and mortality in infants born in the United States, especially among black infants. Because a newborn can acquire GBS during and after delivery, the Centers for Disease Control and Prevention (CDC) recommends that pregnant women be screened for rectovaginal GBS colonization during the antepartum period between weeks 35 and 37 of gestation and, if they are colonized, that intrapartum antibiotic prophylaxis be administered. A prospective investigational study was undertaken from 2 May 2006 to 14 August 2006 at three sites to establish the performance characteristics of the Smart GBS LB assay on the SmartCycler II system for detecting GBS colonization in subjects in the antepartum period from combined vaginal/rectal swab-based specimens after broth enrichment. Results were compared to broth enrichment culture and to the predicate device, the BD GeneOhm StrepB direct assay. The collected specimens were randomized for swab testing order. Each swab sample was processed simultaneously by culture, Smart GBS LB assay, and the BD GeneOhm StrepB assay. A total of 310 subjects were enrolled, with 306 subject results included in the study. Compared to enrichment culture, the Smart GBS LB assay demonstrated a sensitivity, specificity, positive predictive value, and negative predictive value of 98.6%, 90.4%, 77.1%, and 99.5%, respectively. The Smart GBS LB assay demonstrated substantially equivalent or better performance than culture or the predicate device. Screening of broth enrichment fluids by nucleic acid amplification testing requires careful handling during sample processing to avoid possible contamination.